Studies on Homalomeneae (Araceae) of Borneo V: A New Species and New Supergroup Record, of Homalomena from Sabah, Malaysian Borneo - Baharuddin Sulaiman,; Peter C. Boyce, (Tropical Life Sciences Research, 2010)
Homalomena galbana Baharuddin S. & P.C. Boyce is described from the Maliau Basin Conservation Area, Sabah, representing the first species of the Homalomena Supergroup to be recorded from Sabah, and the first mesophytic species of the Supergroup to be described from Borneo. The species is illustrated and a brief discussion on the pollination role of interpistillar staminodes is presented. Homalomena galbana Baharuddin S. & P.C. Boyce dihuraikan dari kawasan Pemuliharaan Maliau Basin, Sabah, mewakili spesies jenis pertama dari Supergroup Homalomena di Sabah, dan spesies mesofitik pertama dari Supergroup tersebut yang akan dihuraikan dari Borneo. Spesis ini diilustrasikan dan perbincangan singkat mengenai peranan penyerbukan dari staminodes interpistillar dibentangkan.